Misje wybranych banków z perspektywy koncepcji CSR - Świeszczak, Marika; Świeszczak, Krzysztof (Annales. Etyka w Życiu Gospodarczym, 2016)
The way of functioning of commercial banks remained unchanged over the years– from the institutions involved in the distribution of financial products and servicesturned into organizations aspiring to the title of socially responsible entities.This means that its activities include the interests of many groups, such as customers,employees, shareholders, local communities and contractors. The result isthose banks that want to be recognized as socially responsible, take numerousinitiatives in areas not related to the sale, such as protection of the environment,voluntary or society.The directions of banks’ activity are determined by the key values, formulatedin the mission, which defines the core of the organization and lets them standout from the competitors. Institutions socially responsible also in this area shouldtake into account the concept of CSR by pointing to various interest groups andtaking various forms of activity.The aim of the publication is to analyse the content of the missions of selectedcommercial banks from the perspective of the various levels of responsibilityand groups of interest. The article hypothesized that not all of the analysed commercialbanks include in their missions the idea of corporate social responsibility,and those that do are limited to specific areas of action and specific stakeholdergroups. The analysis was conducted on the basis of the contents available on thewebsites of the 10 largest financial institutions in Poland in terms of assets.